(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The scientific work analyses the given definitions for the term neologism in various dictionaries of Macedonian language, other Slavic and non-Slavic languages, as well as in primary school Macedonian language textbooks. In addition, there is also an interpretation of the role of, both, time and lexicographic criterion in the definition of neologisms.